Garapal - Mercado, Pong.; Regal Entertainment (Firm). (Quezon City Regal Entertainment, 2000)
Vasques Rago was double crossed by Prano Peret after a gold heist they conspire to pull off. But Vasquest survives his post-heist slaughter with the help of Millie.
VCD
Story and screenplay by Glenn Marcelo ; executive producer Lily Monteverde ; directed by Pong Mercado
Gary Estrada, Tonton Gutierrez, Samantha Lopez, Lara Fabregas
Keywords: Action films; Feature films